2017
DOI: 10.1021/acs.nanolett.7b01504
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying and Elucidating Thermally Enhanced Minority Carrier Diffusion Length Using Radius-Controlled Rutile Nanowires

Abstract: The minority carrier diffusion length (L) is a crucial property that determines the performance of light absorbers in photoelectrochemical (PEC) cells. Many transition-metal oxides are stable photoanodes for solar water splitting but exhibit a small to moderate L, ranging from a few nanometers (such as α-FeO and TiO) to a few tens of nanometers (such as BiVO). Under operating conditions, the temperature of PEC cells can deviate substantially from ambient, yet the temperature dependence of L has not been quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…3d). These two features are in agreement with the reports on the influence of temperature on PEC water splitting performance [36][37][38][39] The reduced photogenerated voltage of the photoelectrodes, prolonged diffusion distance of minority carriers and improved surface catalytic activity with the increase of electrolyte temperature have been proposed to be main reasons. These features suggest that the increased V oc of the thermoelectric-PEC cell with the temperature increase is caused by the voltage input from the thermoelectric device.…”
Section: Thermoelectric Voltage Promoted Pec Water Splitting In a Thrsupporting
confidence: 91%
“…3d). These two features are in agreement with the reports on the influence of temperature on PEC water splitting performance [36][37][38][39] The reduced photogenerated voltage of the photoelectrodes, prolonged diffusion distance of minority carriers and improved surface catalytic activity with the increase of electrolyte temperature have been proposed to be main reasons. These features suggest that the increased V oc of the thermoelectric-PEC cell with the temperature increase is caused by the voltage input from the thermoelectric device.…”
Section: Thermoelectric Voltage Promoted Pec Water Splitting In a Thrsupporting
confidence: 91%
“…Chueh's group has evaluated the temperature-dependent photocurrent of α-Fe 2 O 3 , [144] BiVO 4 , [145] and reduced TiO 2 [146] and found that the minority carrier diffusion length, L D , increased with heating of the semiconductor material. Figure 11a shows that the diameter-dependent photocurrent generated by TiO 2 nanowires increased monotonically with increasing temperature (from 10°C to 70°C).…”
Section: Thermal Effectsmentioning
confidence: 99%
“…a,b) Reproduced with permission. [146] Copyright 2017, American Chemical Society. c,d) Reproduced with permission.…”
Section: Thermal Effectsmentioning
confidence: 99%
“…The reasons for this are twofold, firstly the unfavourable morphology measured by SEM indicates a loss in surface area, restricting the access to electrolyte. Secondly, electronhole recombination stifles the performance of thick Fe 2 O 3 film, due to the short minority carrier path length in α-Fe 2 O 3 [42]. This is evidenced by the largest charge transfer resistance, R CT , indicated by the greatest arc radius in its Nyquist plot, figures S6(A) and (B).…”
Section: Band Structure and Water Splitting Performancementioning
confidence: 99%